PENDAMPINGAN PEMBELAJARAN SISWA SEKOLAH DASAR DI DESA SUNGAISELAN ATAS PADA MASA PANDEMI COVID-19 - Fitri Apriani; Nadia Nadia; Ika Agustianingsih; Desy Sartika; Devi Ridhanti; Helda Helda (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Tutoring assistance is the one of effort in improving teaching and learning process in Covid-19 pandemic era. Nowadays, the government policy is changed the patterns ofeducation system in Indonesia, from offline system become online system. This case, make the students a little confused in application process. This factors caused by various obstacles like internal factores and external factores. The most of obstacle is they have trouble when acquiring learning material maximally. While educational background of their parents average graduated from elementary school so they have the lack of knowledge when resolve their children assignments appropriately. The aim of this program is to improve students’ ability in understanding learning material. The method that used in this program is discourse, discussion, and exercise.